Sexual Behavior and its Relationship with Semen Quality Parameters in Jaffrabadi Breeding Bulls - Chaudhart, JK; solanki, JB; Vijeyta, HP; Gamit, PM; Murthy, KS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was carried out on 80 ejaculates, 20 each from four healthy Jaffrabadi breeding bulls to see the relationship betweensexual behavior and semen quality parameters. The results depicted that the overall mean values of libido score, mating ability score andsexual behavior score of four bulls were 45.83 ± 1.04, 78.79 ± 0.82 and 63.81± 0.77, respectively, with significant (p
Keywords: Correlation; Sexual behavior; Jaffrabadi bulls; Semen quality